Effect of phacoemulsification on intraocular pressure, inflammatory changes and visual acuity in cataract patients - Usharani, Laishram; Debnath, Subhankar; ., Lipokyanger; Meitei, Yumnam Chingsuingamba (International Journal of Research in Medical Sciences, 2022)
Background: Cataract is the leading cause of blindness worldwide. Even in India cataract is the most significant cause of bilateral blindness. For cataract extraction, phacoemulsification is the most commonly done surgery. This study aims to identify the effect of phacoemulsification in terms of intraocular pressure, inflammatory changes and visual acuity. Methods: A cohort study was conducted in the Department of Ophthalmology, RIMS, Imphal from September 2017 to August 2019 among 218 patients who underwent phacoemulsification surgery. Post-operative examination of visual acuity with snellen visual acuity chart, slit lamp biomicroscopy for anterior chamber reaction and non contact tonometry for measuring IOP was done on day 1, 3, 7, 30 and 90 respectively. Results: Majority (41.3%) of the patients belonged to the age group of 61-80 years. Females (53.70%) were affected more than the males (46.30%). There was a significant improvement of visual acuity following phacoemulsification with 73.9% patient achieving a vision of 6/6-6/18 on day 1 and 100% achieving best corrected visual acuity of 6/6-6/18 at the end of 1 month. Majority of the patients (71.1%) had grade 1 cells in anterior chamber on day 1.By the end of one week only 11.5% had grade 1 cells and no cells were seen by the end of one month. There was a significant (p<0.001) decrease in IOP on different postoperative days. Conclusions: We observed that there was a significant improvement in the visual acuity following phacoemulsification surgery which was comparable to the World Health Organization’s recommendations. Majority had mild anterior chamber reaction which was subsided consequently. Also, there was a significant decrease of IOP post surgery.